The Diversity of Fibrillin Functions: Lessons from the Periodontal Ligament - Elisabeth Genot; Tala Al Tabosh; Sylvain Catros; Florian Alonso; Damien Le Nihouannen (Cells)
Marfan syndrome is caused by a mutation in the FBN1 gene encoding fibrillin-1. This extracellular matrix glycoprotein, which assembles into microfibrils, is best known for its scaffolding role in the production of elastic fibers responsible for connective tissue elasticity and tensile strength. Research into Marfan syndrome mainly focuses on the pathophysiology involved in the degeneration of elastin-rich elastic fibers, which are essential components of the aortic wall. However, fibrillin-1 also exists in elastin-poor (elaunin) or elastin-free (oxytalan) microfibril bundles that were first described in the periodontal ligament (PDL). This dynamic, densely cellular, and highly vascularized tissue anchors teeth in their bone sockets and acts as a protective shock absorber during chewing. Current knowledge suggests that fibrillin microfibrils mechanically support blood vessels in the PDL and ensure their proper functioning. However, many more insights on the roles of fibrillin, especially independently of elastin, can be extracted from this tissue. Here, we review the phenotypic and functional characteristics of the PDL in connection with fibrillin-1, focusing on those related to microvessels. This review aims to shed light on this often-overlooked fibrillin-rich resource as a model for future studies investigating fibrillin functions in health and Marfan disease.